SPICE-like Models for Nonlinear Capacitors and Inductors - Iordache, Mihai; Dumitriu, Lucia; Perpelea, Mircea; Sîrbu, Ioana-Gabriela; Mandache, Lucian (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Some new models for nonlinear capacitors and nonlinear inductors built with SPICE-like element primitives are presented here. They have the advantage that they can be used for simulation in SPICE of those circuits which contain nonlinear capacitors controlled either in voltage or in charge, and nonlinear inductors controlled either in current or in flux. These SPICE-like models contain current sources whose controlling variables are charge time-derivative and sources whose controlling variables are flux time-derivative. For validation, the models are included in nonlinear circuits; their behavior is studied by simulation using two different simulators and the results are compared.